2015
DOI: 10.1002/ceat.201500037
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Separation Processes in Decanter Centrifuges by Considering the Sediment Build‐Up

Abstract: Mathematical modeling of the separation process in counter‐current decanter centrifuges was performed, taking into account the influence of the sediment build‐up and the flow pattern. Thus far, separation processes in centrifuges have been calculated by means of simplified empirical models based on the so‐called sigma theory. To reduce experimental efforts, a new model was developed that describes the separation process by considering material functions for sedimentation and the gel point. In addition, an aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
2
19
0
3
Order By: Relevance
“…Whether a particle of a specific size is separated or leaves the centrifuge with the fluid depends on the ratio of the residence time of flocs to the sedimentation time of flocs . To obtain information on the minimum floc diameter that will settle out in the centrifuge, the Stokesian sedimentation velocity is compared with the law of mass conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Whether a particle of a specific size is separated or leaves the centrifuge with the fluid depends on the ratio of the residence time of flocs to the sedimentation time of flocs . To obtain information on the minimum floc diameter that will settle out in the centrifuge, the Stokesian sedimentation velocity is compared with the law of mass conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Im Gegensatz zum Stand der Technik wird außerdem der Sedimentaufbau und der Sedimenttransport bei der Berechnung von Dekantierzentrifugen berücksichtigt . Das Lösen der Massenbilanz der Feststoffphase ergibt die Massenverteilung des Sediments entlang des Schneckenkanals.…”
Section: Dynamische Modellierung Der Prozessebene Und Echtzeit‐simulaunclassified
“…Dies beinhaltet auch die Einbindung von Energie‐ und Rohstoffeffizienz, Kosten, Lebenszyklus sowie die dazugehörigen Optimierungstools . Die Kopplung von Simulationsverfahren (Fluid‐, Struktur‐, Partikel‐, Molekularsimulation etc.) auf mehreren Ebenen erscheint ein möglicher Weg zur ganzheitlichen Betrachtung partikulärer Prozesse ; allerdings immer im Hinblick auf eine Echtzeit‐Simulation mit Short‐cut‐Modellen mit dem nur unbedingt notwendigen Detailierungsgrad. Prädiktive Prozesssimulationen sind derzeit nicht möglich, würden jedoch eine vorausschauende Steuerung und Regelung erlauben. Aufgrund der komplexen Materialparameter ist ein klassischer Scale‐up anhand der üblichen auf Kennzahlen basierenden Methoden nicht mehr zielführend . Prozess‐Simulationen auf der Makroskala, in denen auch das komplexe Materialverhalten abgebildet ist, sind dafür jedoch ein nicht mehr zu vernachlässigendes Werkzeug . Big Data ist ein weiteres in der Industrie 4.0 häufig benutztes Schlagwort.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Self-developed and standard approaches for the simulation of turbulent multiphase flows are known in literature [6]. While some researchers investigated the separation process in centrifuges with CFD [7][8][9][10], others took the influence of the sediment buildup into account [9,11,12]. Breitling et al [7] observed that fully in time and spatially resolved simulations of the flow conditions are needed for the prediction of the separation process in semi-or continuous centrifuges.…”
Section: Introductionmentioning
confidence: 99%